2022
DOI: 10.1021/acsami.2c01739
|View full text |Cite
|
Sign up to set email alerts
|

Degradation-Kinetics-Controllable and Tissue-Regeneration-Matchable Photocross-linked Alginate Hydrogels for Bone Repair

Abstract: Photocross-linked alginate hydrogels, due to their biodegradability, biocompatibility, strong control for gelling kinetics in space and time, and admirable adaptability for in situ polymerization with a minimally invasive approach in surgical procedures, have created great expectations in bone regeneration. However, hydrogels with suitable degradation kinetics that can match the tissue regeneration process have not been designed, which limits their further application in bone tissue engineering. Herein, we fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…71,72 The fast degradation rate of biomaterials shows no pro-osteogenic effect, while a slow degradation rate delays the progress of bone formation. 73 Here, the degradation time of the CGP hydrogels was similar to the time required for rat bone healing, suggesting the potential application of the hydrogels for bone defect repair. 74 Furthermore, H&E staining of hydrogel with surrounding tissues was performed to reveal adjacent tissue responses and histological changes after hydrogel implantation (Figure 6d).…”
Section: 5supporting
confidence: 54%
See 1 more Smart Citation
“…71,72 The fast degradation rate of biomaterials shows no pro-osteogenic effect, while a slow degradation rate delays the progress of bone formation. 73 Here, the degradation time of the CGP hydrogels was similar to the time required for rat bone healing, suggesting the potential application of the hydrogels for bone defect repair. 74 Furthermore, H&E staining of hydrogel with surrounding tissues was performed to reveal adjacent tissue responses and histological changes after hydrogel implantation (Figure 6d).…”
Section: 5supporting
confidence: 54%
“…The result suggested that the addition of LPRFe did not influence the biodegradation time of CG hydrogels. The degradation rate of biomaterials used for bone tissue engineering is expected to match the bone regeneration rate. , The fast degradation rate of biomaterials shows no pro-osteogenic effect, while a slow degradation rate delays the progress of bone formation . Here, the degradation time of the CGP hydrogels was similar to the time required for rat bone healing, suggesting the potential application of the hydrogels for bone defect repair …”
Section: Results and Discussionmentioning
confidence: 77%
“…In the physiological milieu, alginate hydrogel degradation is uncontrolled, and the molecular weight of released alginate strands is often higher than the renal clearance threshold. To control the degradation rate, oxidized alginate and cleavable crosslinkers have been applied in smart hydrogels, making them sensitive to specific stimuli [ 36 , 37 ].…”
Section: Polymers For Smart Hydrogelsmentioning
confidence: 99%
“…Studies have shown that the alginate gel can load and culture bone marrow stromal cells (BMSC), which can form bone structures. 207 Taking cartilage repair as an example, the implantation of mixed alginate hydrogel scaffolds into the knee joint defect can induce the promotion of cartilage reconstruction, 208 or the artificial composite alginate hydrogel is directly used to replace some cartilage tissues. 209,210 Adding hydroxyapatite into the sodium alginate hydrogel for wound healing can stimulate the natural growth of living tissue and the recovery of damaged parts of the body.…”
Section: Sodium Alginate Hydrogels For Wound Therapymentioning
confidence: 99%